1994
DOI: 10.1007/bf00139104
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of some rhodium(III) cyclometallated complexes of 2-substituted benzylideneamino thiazoles

Abstract: Schiff's bases derived from 2-aminothiazole and substituted benzaldehydes were reacted with [RhCI(PPh3)3] or [Rh-(/~-CI)(COD)] 2 (COD = 1,5-cyclooctadiene) in the presence of four equivalents of PPh3 to give Rh m cyclometallated complexes of the type [RhHCI{ (X-benzylidene) thiazole}-(PPh3)2], in which the imine C H added oxidatively to the metal. The complexes were characterized using i.r., u.v. and n.m.r, spectroscopy. The disposition of the hydride ligand was inferred as trans to a N-donor ligand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…data in agreement with the reported literature value [17,[22][23][24][25][26]. The newly described compounds 9, 11−14 were confirmed by elemental analyses and by IR, MS and H 1 -…”
Section: Chemistrysupporting
confidence: 90%
“…data in agreement with the reported literature value [17,[22][23][24][25][26]. The newly described compounds 9, 11−14 were confirmed by elemental analyses and by IR, MS and H 1 -…”
Section: Chemistrysupporting
confidence: 90%
“…from the metal-bonded carbon, C (7) (iminoyl carbon-13C=N) appears as a doublet of triplets owing to coupling to two equivalent 31P nuclei and the 103 Rh nucleus, whereas the corresponding signal from the uncomplexed Schiff base was found at 159.25-164.97 ppm [24]. For C (7), -has been observed at low-field position in which a chelating atom is incorporated in a five member-ring [33], and this was expected for a cyclometallated sp 2 carbon [11,34] (similar to carbene-carbon. The remaining 1 H and 13 C NMR data are as expected.…”
Section: Resultsmentioning
confidence: 99%
“…The first report of ortho-metallation of imines at rhodium via C-H activation has appeared only recently [2][3][4]10]. Interestingly, cyclometallation reaction of imine [11] C-H bonds leads us to study some of the important chemistry related to the imines, derivatives from 2-aminothiazole and its derivatives and aryl aldehydes. In most recent application for ruthenium, rhodium and iridium complexes have been used as therapeutic agents and a number of kinetically inert ruthenium(II), iridium(III) and rhodium(III) complexes have been reported as inhibitors of protein kinases [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Although the Cyclometallation of aromatic and to a lesser extent aliphatic C-H groups is widely recognized [1,2], these are relatively little known concerning with the cyclometallation of aldehydes [3] and imine functions [4][5][6]. We have shown that Schiff bases of 2-substituted benzylideneaminothiazoles [5], and 2-(benzylideneamino) pyridines [6], can be form cyclometallated complexes at the imine carbon by using Rh (I) complex. A number of studies have exploited ligands such as quindine-8-carbaldehyde [3,7] and 2-(benzylideneamino) pyridines [8].…”
Section: Introductionmentioning
confidence: 99%